Economic-Mathematical Modeling of the Enterprise Solvency Risk Assessment - Alekseevich, Yakushev Anatoly; Valentinovna, Lysenko Yulia (International Journal of Economics and Financial Issues, 2018)
This article describes the methodological approaches to the development of a model of capital structure optimization analysis taking into account the factors affecting the ratio of capital structure optimization: the criterion of return on equity maximization with a minimum level of financial risks. In the process of selecting the optimal source of funding, both quantitative and qualitative indicators of the availability of funding channels were evaluated. A significant role is played by the evidence schemes of the practical application of the model, which contributes to the growth of capital, and increase its share in the overall structure of sources of financing. The purpose of this paper is to present a methodological approach to the development of capital structure optimization analysis model. As a measure of dependence factor analysis of return on equity is used. It is shown that the factor model takes into account various methodological approaches to the development of evaluation of the structure of sources of financing activities, the efficiency of use of equity and debt capital, the development of management decisions aimed at optimizing the capital structure to increase capital productivity. This article uses regression analysis to predict the profitability of financial activities. Keywords: solvency, cash flows, analysis model, risk assessment, balance liquidity, finance, comparative analysis, liabilities JEL Classifications: Q12, O18, R51 DOI: https://doi.org/10.32479/ijefi.7178